Crecimiento, equidad y pobreza - Peñaranda Castañeda, César (2001)
The paper discusses in general terms the problem of equity and poverty at international level and in more profound and specific way the case of Peru. The paper has been organized in four sections, the first one presents a general view of the topics in order to know its meaning and scope. The second and third sections analyse the diagnosis and reasons respectively of the income distribution and poverty in Peru. Finally the last section covers the recommendation of how to deal and solve both problems at national and international level.